Pengaruh Co-Branding, Tren Fashion, dan Kelompok Acuan Terhadap Keputusan Pembelian Sepatu Vans (Studi Kasus Mahasiswa Universitas Mulawarman) - Witjaksana, Andhika; Wasil, Muhammad (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of co-branding, fashion trends, and reference groups on the purchase decisions of Vans shoes among students of Mulawarman University. The research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to 112 respondents selected via purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that partially, co-branding and reference groups have a positive and significant effect on purchase decisions, while fashion trends do not have a significant effect. Simultaneously, all independent variables significantly influence purchase decisions with a strong correlation level. The coefficient of determination shows that 39% of the variation in purchase decisions can be explained by the research model, while the remaining 61% is influenced by other factors outside the model. These findings suggest that co-branding strategies and social influences play a more dominant role in shaping students’ purchase decisions compared to dynamic fashion trends. This study is expected to contribute to the development of marketing knowledge and provide practical insights for businesses in designing more effective marketing strategies.